Perancangan Sistem Inventarisasi Sarana sebagai Upaya Peningkatan Akreditasi Sekolah di SMAN 5 Pamekasan - Imdadur Rohman; Zeinal Abidin; Eka maftuhatil Riskiyah; Abdul Aziz (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine the process of designing a facility inventory system as an effort to increase school accreditation at SMAN 5 Pamekasan. The research method used is a qualitative research method, with a descriptive type. Data collection techniques include observation, interviews and documentation. The findings of this research show that the inventory manager is the administrative party and the administrative inventory is commanded by the school principal by involving teachers and students. The inventory of SMAN 5 Pamekasan has its essence as an effort to improve, manage and supervise existing facilities at SMAN 5 Pamekasan. There are two versions of the media or inventory design system for the Regional Goods and Asset Management Information System (SIMBADA), and they are carried out manually or written in accordance with the inventory master book. This media is specifically designed to solve problems related to asset inventory. In managing regional assets owned by the government. This makes it easier for the SMAN 5 Pamekasan institution in the process of improving accreditation and school quality. Conclusion, that in the inventory of facilities a system or model must be implemented that suits the needs of the institution, to help improve the school accreditation process and expedite the process of inventory of facilities according to their portion and placement. Key Words: Designing Inventory of Facilities, Increasing School Accreditation